1133. Investigation of Treatment-Emergent Amino Acid Substitutions in Nonstructural Protein 5 from Ph2a Study of Ensitrelvir, a Novel Oral SARS-CoV-2 3C-Like Protease Inhibitor. (15th December 2022) - Sanaki, Takao; Baba, Keiko; Yamamoto, Atsuko; Nobori, Haruaki; Uehara, Shota; Kajiwara, Yoko; Yoshida, Ryu; Sakaguchi, Hiroki; Hasegawa, Takahiro; Hatanaka, Akifumi; Ichihashi, Genki; Takeda, Yosuke; et al.
Abstract: Background: Ensitrelvir is a novel oral SARS-CoV-2 3C-like protease inhibitor, and under late clinical development stage for COVID-19 disease. In Ph2a and Ph2b studies, ensitrelvir demonstrated rapid decline of viral titer and viral RNA compared with placebo, and tolerability. To investigate treatment-emergent amino acid substitutions (TEAASs), we analyzed viral RNA sequences of nonstructural protein 5 (NSP5), target of ensitrelvir from Ph2a study in Japan. Methods: In Ph2a study, 69 patients with confirmed SARS-CoV-2 infection were randomized 1:1:1 to ensitrelvir with the loading dose on Day 1/maintenance dose on Day 2-5 (375/125 mg or 750/250 mg), or placebo. Intent-to-treat (ITT) population was defined as participants confirmed with positivity by qualitative RT-PCR at baseline. TEAASs were defined as novel amino acid substitutions identified after treatment with ensitrelvir. NSP5 sequence analysis was performed with sanger sequencing using nasopharyngeal swab samples at Day 1, 6, 9, 14, and 21 with allowances from ITT population with ensitrelvir. Infectious viral titer was measured by virus-induced cytopathic effects in VeroE6/TMPRSS2 cells. Viral RNA was quantified by RT-PCR. Results: By NSP5 sequence analysis, TEAASs were observed in 1 patient from 375/125 mg group and 2 patients from 750/250 mg group. H246Y in 375/125 mg was detected from specimen on Day 8, and A234S and T198I in 750/250 mg were detected from specimens on Day 8 and Day 14, respectively. Structural analysis revealed that these mutations are located outside of the active center of 3C-like protease which is the binding site of ensitrelvir. Viral titer and viral RNA in each specimen, in which TEAASs were observed, were below lower limit of detection and lower limit of quantification, respectively. Furthermore, H246Y, A234S and T198I are rare substitution (< 0.05%) among SARS-CoV-2 variants according to Global Initiative on Sharing Avian Influenza Data. Conclusion: In Ph2a study, H246Y, A234S, and T198I in NSP5 were detected as TEAASs. However, results of viral titer and viral RNA, and structural information suggest that these mutations do not have the impact on antiviral efficacy of ensitrelvir. Disclosures: All Authors : No reported disclosures.